DMAP‐BODIPY Alkynes: A Convenient Tool for Labeling Biomolecules for Bimodal PET–Optical Imaging1. Issue 40 (21st August 2014) - Brizet, Bertrand; Goncalves, Victor; Bernhard, Claire; Harvey, Pierre D.; Denat, Franck; Goze, Christine
Abstract Several new boron dipyrromethene/N, N‐dimethylaminopyridine (BODIPY‐DMAP) assemblies were synthesized as precursors for bimodal imaging probes (optical imaging, OI/positron emission tomography, PET). The photophysical properties of the new compounds were also studied. The first proof‐of‐concept was obtained with the preparation of several new BODIPY‐labeled bombesins and evaluation of the affinity for bombesin receptors by using a competition binding assay. Fluorination reactions were investigated on DMAP‐BODIPY precursors as well as on DMAP‐BODIPY‐labeled bombesins. Chemical modifications on the BODIPY core were also performed to obtain luminescent dyes emitting in the therapeutic window (650–900 nm), suitable for in vivo imaging, making these compounds promising precursors for PET/optical dual‐modality imaging agents.